Gestational Tubal Choriocarcinoma Presenting as a Pregnancy of Unknown Location following Ovarian Induction - Lawrence Hsu Lin; Koji Fushida; Eliane Azeka Hase; Regina Schultz; Laysa Manatta Tenorio; Fabricia Andrea Rosa Madia; Evelin Aline Zanardo; Leslie Domenici Kulikowski; Rossana Pulcineli Vieira Francisco (Case Reports in Obstetrics and Gynecology)
The management of pregnancy of unknown location (PUL) can be a challenging situation, since it can present as several different conditions. Here we describe a rare case of gestational choriocarcinoma arising in the fallopian tube after ovarian induction in an infertile patient. The patient received clomiphene for ovarian induction and had rising levels of human chorionic gonadotropin (hCG) over nine months without sign of pregnancy. After referral to our center, the patient was diagnosed with a paraovarian tumor, which revealed a gestational choriocarcinoma arising in the fallopian tube; the final diagnosis was supported by pathological and cytogenomic analysis. Malignancies, such as gestational trophoblastic disease, should be in the differential diagnosis of PUL; the early recognition of these conditions is key for the proper treatment and favorable outcome.